Flexor Tendon Repair Postoperative Rehabilitation: The Saint John Protocol. Issue 11 (November 2016) - Higgins, Amanda; Lalonde, Donald H.
Abstract : Summary: The Saint John Protocol describes a rehabilitation program of up to half a fist of protected true active finger flexion beginning 3 to 5 days after flexor tendon repair. We no longer use full fist place and hold. We illustrate with film and text the reasons for these changes. Abstract : Supplemental Digital Content is available in the text.